Inter-relationship between ageing, body mass index, diabetes, systemic blood pressure and intraocular pressure in Asians: 6-year longitudinal study. Issue 2 (9th April 2018) - Chua, Jacqueline; Chee, Miao Li; Chin, Calvin Woon Loong; Tham, Yih Chung; Tan, Nicholas; Lim, Sing Hui; Aung, Tin; Cheng, Ching-Yu; Wong, Tien Yin; Schmetterer, Leopold
Abstract : Background: To investigate the biological effect of ageing on intraocular pressure (IOP) and risk factors in a population-based cohort study of Malay and Indian adults. Methods: Participants aged 40–80 years were recruited for baseline and 6-year follow-up visits between 2004–2009 and 2010–2015, respectively. Blood pressure (BP) was measured with an automatic BP monitor and IOP were obtained by Goldmann applanation tonometry. Main outcome was change in IOP, defined as the difference between the 6-year IOP and the baseline IOP. Linear regression models were used to investigate the association of changes in IOP with risk factors. Results: Participants without a history of glaucoma or cataract surgery at baseline were included (n = 3188; mean age: 54±9 years) . Their average IOP was reduced (−0.5±3.1 mm Hg), except for those who developed hypertension at follow-up (0.0±3.1 mm Hg). After adjusting for covariates, changes in IOP were negatively associated with age (β=−0.07, 95% CI −0.13 to −0.01) and positively associated with body mass index, diabetes, hypertension (normotensive as reference group; newly developed hypertensive (β=0.67, 95% CI 0.39 to 0.95) and chronic hypertensive (β=0.46, 95% CI 0.22 to 0.70)), baseline systolic BP (SBP) (β=0.20, 95% CI 0.14 to 0.26) and diastolic BP (DBP) (β=0.33, 95% CI 0.22 to 0.44), as well as with 6-year increases in SBP (β=0.27, 95% CI 0.21 to 0.33) and DBP (β=0.52, 95% CI 0.41 to 0.63). Conclusions: Normal ageing and reduced systemic BP are associated with reduced IOP in Malay and Indian adults. Given that high IOP is a risk factor for glaucoma, our finding highlights the importance of controlling hypertension in older adults, where hypertension and glaucoma incidences are on a rise.